The Nucleotide Sequence of the lac Operator - Gilbert, Walter (Proc Natl Acad Sci U S A, 1973)
The lac repressor protects the lac operator against digestion with deoxyribonuclease. The protected fragment is double-stranded and about 27 base-pairs long. We determined the sequence of RNA transcription copies of this fragment and present a sequence for 24 base pairs. It is: 5′--T G G A A T T G T G A G C G G A T A A C A A T T 3′ 3′--A C C T T A A C A C T C G C C T A T T G T T A A 5′ The sequence has 2-fold symmetry regions; the two longest are separated by one turn of the DNA double helix.